PEMBINAAN MORAL ANAK DI SLB YPLB (YAYASAN PENDIDIKAN LUAR BIASA) DANYANG KECAMATAN PURWODADI KABUPATEN GROBOGAN - Riyandani, Hesty Nurtika (Civic Education Program, Universitas Negeri Semarang, 2017)
The objectives of this research to find out the characteristic of the studentsâ€™ moralityÂ in SLB B YPLB Danyang Kabupaten Grobogan, the morality that is implanted to the studentsâ€™ of SLB B YPLB Danyang Kabupaten Grobogan, and the obstacles faced by the teacher in doing the founding of morality to the students of SLB B YPLB Danyang Kabupaten Grobogan. This research uses qualitative method. The location of this method is in SLB B YPLB Danyang Kecamatan Purwodadi Kabupaten Grobogan. The procedure of data collection uses observation, interview, and documentation techniques. The results of this research show that The characteristic of the morality founding that is applied by SLB B YPLB Danyang is contained in the used curriculum, the process of morality founding, the activity of morality founding, and the implementation time. The values of morality that are implanted to the students of SLB B YPLB are appropriate with the values contained in the Pancasila. The obstacles that are faced in doing the founding of morality in SLB B YPLB Danyang consist of internal and external obstacles. The suggestions of this research are: for school, based on the condition exists, it shows that there are still many teachers with less competent skill. Therefore, school party should do the recruitment of teachers as well as and as objectively as it can.